The Existence of Bahasa Walikan as A Communication Tool in the Social Interactions of Non-Local Students from Universitas Brawijaya - Esta Dyandra; Raisha Anindya Putri; Raissa Rachmania; Sabrina Syafa Nafisah Al Khayira; Nirnando Agung Gumelar; Sabilah Indah Prasasti (Dinamika Bahasa dan Budaya, 2026)
Bahasa Walikan is a dialect unique to the people of Malang, characterized by a linguistic feature known as word phonetic reversal. Bahasa Walikan remains a definitive symbol of Malang’s local cultural identity, yet its continued existence faces significant scrutiny. Its relevance is increasingly put to the test as daily usage shifts within a rapidly changing society. The purpose of this study is to analyze the use and existence of Bahasa Walikan among non-local students at Universitas Brawijaya, given the multicultural student body from outside East Java, which makes it an ideal setting for observing the use of Bahasa Walikan by non-local students. This study employs in-depth qualitative interviews and participant observation among non-local students. The results of the study indicate that non-local students perceive Bahasa Walikan as a vital tool for fostering emotional closeness and social inclusion. However, field data reveal its weak existence in the heterogeneous campus environment, with 72.4% of respondents rarely or never using the language in their daily interactions. This study confirms that Bahasa Walikan is at risk of extinction among university students due to the dominance of the national language and the lack of sustained active use. Without a commitment to and a positive attitude toward the language among its speakers, there is concern that the role of Bahasa Walikan as a symbol of Malang’s local cultural identity will gradually disappear in the future. Keywords: Bahasa Walikan, Existence, Universitas Brawijaya, Non-local students.